A Bibliometric Analysis of Cross-Cultural Communication on Digital Platforms: Mapping Collaboration, Citations, and Research Themes - Safitri, Arroyya Nur; Anwar, Rully Khairul; Winoto, Yunus; Damayani, Ninis Agustini; Kusnandar, Kusnandar (Nyimak: Journal of Communication, 2025)
This study aims to map the research landscape of cross-cultural communication on digital platforms, identify knowledge gaps, and analyze existing trends. Specifically, this research examines the evolution of research, inter-country collaboration, and its impact. Quantitative bibliometric methods were applied to data from the Scopus database (2011–2024), analyzing key indicators such as the number of publications, citations, h-index, keyword trends, and author collaboration networks (co-authorship networks). The results show the dominance of the United States in the number of publications (157) and citations (69), reflecting a strong research ecosystem and global influence. Collaboration network analysis shows that while some countries, such as China, have strong intra-country collaboration (indicated by high Single Country Publications (SCP)), other countries, such as Spain, show more significant international collaboration (Multiple Country Publications/MCP). Developing countries, although their contribution is smaller quantitatively, exhibit unique collaboration patterns that focus on regional and local issues, enriching the global perspective in this research. This study identifies a lack of in-depth studies on specific digital platforms beyond Western-based platforms, as well as the need for further research on the impact of non-Western cultures in online interactions.Keywords: Cross-Cultural Communication, Digital Platforms, Collaboration, Citation, Bibliometrics. ABSTRAKPenelitian ini bertujuan untuk memetakan lanskap penelitian komunikasi lintas budaya di platform digital, mengidentifikasi kesenjangan pengetahuan, dan menganalisis tren yang ada. Secara khusus, penelitian ini mengkaji evolusi penelitian, kolaborasi antarnegara, dan dampaknya. Metode bibliometrik kuantitatif diterapkan pada data dari database Scopus (2011–2024), dengan menganalisis indikator kunci seperti jumlah publikasi, sitasi, h-index, tren kata kunci, dan jaringan kolaborasi penulis (co-authorship networks). Hasil penelitian menunjukkan dominasi Amerika Serikat dalam jumlah publikasi (157) dan sitasi (69), yang mencerminkan ekosistem penelitian yang kuat dan pengaruh global. Analisis jaringan kolaborasi menunjukkan bahwa sementara beberapa negara, seperti Tiongkok, memiliki kolaborasi intra-country yang kuat (ditunjukkan oleh Single Country Publications (SCP) yang tinggi), negara lain, seperti Spanyol, menunjukkan kolaborasi internasional yang lebih signifikan (Multiple Country Publications/MCP). Negara-negara berkembang, meskipun kontribusinya lebih kecil secara kuantitatif, menunjukkan pola kolaborasi unik yang berfokus pada isu-isu regional dan lokal, memperkaya perspektif global dalam penelitian ini. Penelitian ini mengidentifikasi kurangnya studi mendalam tentang platform digital spesifik di luar platform yang berbasis di Barat, serta perlunya penelitian lebih lanjut tentang dampak budaya non-Barat dalam interaksi online.Kata Kunci: Komunikasi Lintas Budaya, Platform Digital, Kolaborasi, Sitasi, Bibliometrik.